Semblance of a physician: medical students' experiences during Type 2 Diabetes Mellitus clinic simulation - Gabriel Lavorato Neto; Egberto Ribeiro Turato; Maria Cândida Ribeiro Parisi (Faculdade de Medicina de Botucatu (Unesp), 2023)
This qualitative research aimed to understand the experiences of a fourth-year medical class during two clinical simulation scenarios of type 2 diabetes management in Primary Care. Ten simulated students were interviewed. The results describe the symbolic conception of diabetes and its treatment as anguish, damage, condemnation and an unpleasant sentence that affects the appropriation and performance of the medical role by students. Considering Medical Psychology, we suggest that such subjective factors should be addressed in teaching-learning in addition to commonly cognitive aspects mentioned in the medical education literature in order for students to develop the work profile to cope with diabetes in Primary Care. Clinical simulation facilitates the subjective approach through its group support component to promote reflection, insights and self-awareness.